Kallmann Syndrome. Case presentation - Elodia Rivas Alpízar; Maidelín Garcés Saborit; Caridad Hernández Gutiérrez; Odalis Yanes Izray (Medisur)
Kallmann syndrome is characterized by the association of hypogonadotropic hypogonadism and anosmia. It affects one of every 10 000 and 50 000 women. It is presented a case of a patient who came to the endocrinology service at the General University Hospital Dr. Gustavo Aldereguía Lima. Cienfuegos, due to pubertal delay and olfactory disorders, characteristics which belong to this syndrome. A cytogenetic hormonal study (FSH; LH, testosterone) was developed, a nuclear MRI of the skull and silla turca in which it was confirmed agenesis of the right olfactory bulb and hypoplastic of the left one. The presentation of the case was decided due to the importance of making an early diagnosis to start substituting hormonal treatment adequately, improve the pubertal growth spurt and bone mineralization, increase muscular mass, so as to avoid psychological disturbances in adolescents with pubertal delay.